2016
DOI: 10.2196/cancer.5212
|View full text |Cite
|
Sign up to set email alerts
|

“Googling” for Cancer: An Infodemiological Assessment of Online Search Interests in Australia, Canada, New Zealand, the United Kingdom, and the United States

Abstract: BackgroundThe infodemiological analysis of queries from search engines to shed light on the status of various noncommunicable diseases has gained increasing popularity in recent years.ObjectiveThe aim of the study was to determine the international perspective on the distribution of information seeking in Google regarding “cancer” in major English-speaking countries.MethodsWe used Google Trends service to assess people’s interest in searching about “Cancer” classified as “Disease,” from January 2004 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…Previous infodemiology literature has examined Web search query data to evaluate various public health and health care research questions. For example, several studies used Web search query data to identify influenza outbreaks ahead of conventional population detection methods in the United States [5-13] and abroad [14-20], as well as other public health surveillance [21-24]. Researchers have also analyzed search queries for the detection and prevention of adverse drug events, or any other drug related complications [25-27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous infodemiology literature has examined Web search query data to evaluate various public health and health care research questions. For example, several studies used Web search query data to identify influenza outbreaks ahead of conventional population detection methods in the United States [5-13] and abroad [14-20], as well as other public health surveillance [21-24]. Researchers have also analyzed search queries for the detection and prevention of adverse drug events, or any other drug related complications [25-27].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies reported moderate to strong degree of associations, suggesting a potential value in applying infoveillance to chronic diseases. Foroughi et al [19] found that cancer-related terms were associated with Web search activity for the burden of cancers, such as cancer incidence and mortality, in Australia, New Zealand, the United Kingdom, Canada, and the United States. Also, an American study showed associations between suicide rates and Google search trends relating to “how to suicide,” “commit suicide,” and “suicide prevention” among all 50 states in 2009 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Internet data mining has already shown a great potential to elucidate public attitudes associated with the consumption of health information [Bakker et al, 2016;Foroughi et al, 2016]. Google Trends is an online tool that evaluates a percentage of billions of daily structured queries entered into Google Search, the leading company in the industry of search engines [NetMarketShare, 2016].…”
mentioning
confidence: 99%